2019
DOI: 10.3390/cancers11111752
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear but Not Polymorphonuclear Phagocyte Depletion Increases Circulation Times and Improves Mammary Tumor-Homing Efficiency of Donor Bone Marrow-Derived Monocytes

Abstract: Tumor associated macrophages are an essential part of the tumor microenvironment. Consequently, bone marrow-derived monocytes (BMDMs) are continuously recruited to tumors and are therefore seen as ideal delivery vehicles with tumor-targeting properties. By using immune cell depleting agents and macroscopic in vivo fluorescence imaging, we demonstrated that removal of endogenous monocytes and macrophages (but not neutrophils) leads to an increased tumor accumulation of exogenously administered BMDMs. By means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Finally, FLI and BLI are not mutually exclusive and can be used in parallel [129] , as fusion proteins [130] , and as BRET partners (section 5.2.2).…”
Section: Other Techniques That Could Reach Ema/fda Requirementsmentioning
confidence: 99%
“…Finally, FLI and BLI are not mutually exclusive and can be used in parallel [129] , as fusion proteins [130] , and as BRET partners (section 5.2.2).…”
Section: Other Techniques That Could Reach Ema/fda Requirementsmentioning
confidence: 99%
“…Removing the spleen before injection of immune cells resulted in increased liver accumulation of these cells, but their short-term trafficking to tumors remained unaffected [328]. This key observation could indicate that the luminal surface of the tumor vasculature is saturated with endogenous immune cells, hindering injected cells to find an available attachment site [329]. Consequently, intratumoral cell accumulation is a gradual process that requires multiple days or even weeks to complete.…”
Section: Employing Nanoparticles To Load Tumor-targeting Immune Cellsmentioning
confidence: 99%
“…Interestingly, masking phosphatidylserine exposure via annexin V prevented subsequent phagocytosis and could therefore be explored as a way to decrease the arrest of adoptively transferred immune cells in organs participating in efferocytosis [333]. Our group has recently demonstrated that depleting the MPS via pretreatment with clodronate liposomes drastically increased both the circulatory half-life and tissue accumulation efficiency of infused bone marrow-derived monocytes [329]. In addition, no change in monocyte distribution pattern was observed after depletion of endogenous neutrophils [329].…”
Section: Employing Nanoparticles To Load Tumor-targeting Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology rendered multiple therapeutic benefits, including an increased delivery of IL-15, an intratumoral increase of CD8 + T cells, and consequently, an improved CAR-T cell response [50] . As immune cell isolation, ex vivo manipulation and subsequent systemic re-infusion may lead to the rapid recognition of the injected cells by the mononuclear phagocyte system via e.g., efferocytosis [51,52] , we speculate that such ex vivo approaches can be refined and improved by performing direct in vivo targeting of immune cells. In vivo immune cell targeting also provides the possibility of inhibiting (or even killing) immune cells in the circulation, thereby modulating the number and type of immune cells infiltrating tumors and metastases.…”
Section: Benefits Of In Vivo Immune Cell Targetingmentioning
confidence: 99%